Consumer Work and Agency in the Analog Revival - Beverland, Michael B; Fernandez, Karen V; Eckhardt, Giana M (Journal of Consumer Research, 2024)
Abstract Why do consumers choose difficult analog technologies over their labor-saving digital counterparts? Through ethnographic investigations of three once defunct analog technologies that have experienced a resurgence (vinyl music, film photography, and analog synthesizers), we explore how the act of consumer work enables consumers to experience shifting dimensions of agency. We utilize the theoretical lens of serious leisure to introduce a four-stage work process (novice, apprentice, craft, and design) in which the experience of agency is dependent on the shifting relations between user, object, and context. The four stages are cumulative and conjunctive, representing the development of skills toward mastery while also being connected via three transition mechanisms (contextualization, schematization, and hypothesization) that address agency–alienation tensions. The transition through these mechanisms is necessary to sustain emotional engagement in consumer work. Our contribution lies in demonstrating the myriad of ways in which consumer work as serious leisure generates different experiences of agency and alienation and the ways in which consumers can sustain engagement in their work.